TE-like mode analysis of microsystem InGaAsP/InP semiconductor resonator generating 20 GHz repetition rate pulse trains - Amiri, Iraj Sadegh; Anwar, Toni; Zakaria, Rozalina; Yupapin, Preecha Promphan (Elsevier, 2018)
In microsystem technologies, the microring resonators (MRRs) can be used as a filter device. A wavelength-selective modified add-drop MRR filter is used for adding and dropping a particular wavelength in order to control the light propagation within the system. The spectrum of the mode-locked laser could be generated using a fiber laser loop consisting of active gain medium, EDF, Lumics 980 nm laser diode (LD), wavelength division multiplexer (WDM), isolator, a polarization controller (PC) and carbon nanotube (CNT). The multi-mode-locked laser could be generated at the through and drop port of the system after the mode-locked pulse from the fiber laser circulate within the MRR filter. Here, the mode-locking relies on a fiber laser setup, where the MRR filter has been modeled using the Fimmwave and PICWave softwares. We present this photonic circuits simulator based on the time-domain traveling wave (TDTW) method, provides modeling both active and passive photonic circuits. The pulse bandwidth and repetition of the train mode-locked pulses generated by the fiber laser setup are 0.65 ps and 30 MHz respectively. Using the MRR filter, the drop port output pulses show the FSR and FWHM of 172 pm (20 GHz) and 8.3 pm respectively. The finesse and the Q-factor are approximately 20.72 and 1.9 × 105 respectively.